Pengembangan Media Pembelajaran Pop Up Book Materi Kearifan Lokal Budaya Nusantara - Dionisius Heckie Puspoko Jati; Nani Mediatati; Rakhel Dwi Kristiani (LPPM Universitas 17 Agustus 1945 Semarang, 2025)
This research aims to develop a pop-up book-based learning media to introduce local wisdom of Indonesian culture to the younger generation. Local wisdom, as an inheritance of knowledge and values from our ancestors, is a national identity that is increasingly poorly understood by the current generation. Therefore, an interesting, creative, and interactive learning media innovation is needed. Pop-up books were chosen because of their ability to present material visually, lively, and allow students to interact directly with the learning content. This research uses the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The process starts from needs analysis, book design development, prototyping, to trials for grade XI students of SMK. The research instruments included validation questionnaires from material experts, media experts, teacher and student responses, and material comprehension tests. The validation results showed scores of 82.8% (material experts), 78.3% (media experts), and 75.5% (potential user responses), which overall fell into the very feasible category. The findings of the study show that pop-up book media is effective in increasing students' understanding of local wisdom in the context of Bhinneka Tunggal Ika. In addition, this research contributes to the preservation of local culture through educational media innovation. This pop-up book media is expected to be an interesting, interactive, and relevant learning solution for students in understanding the diversity of Indonesian culture.